Five-coordinate zinc(ii) complexes containing sterically demanding bio-mimetic n3s2 ligands. Syntheses, characterization and dft calculations - Shaban, Shaban Abd El Fattah Youssef; Puchta, Ralph; van Eldik, Rudi (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2010)
In search of complexes having [ZnN3S2] cores in the monomeric form with trans-thiolate donor atoms, new sterically demanding tri- and pentadentate ligands containing biomimetic N3S2 cores have been synthesized. The reaction of bis(2-mercapto-3,5-di-tert-butylaniline) zinc(II) with 2,6-diacetylpyridine leads to the formation of the zinc imine [Zn(pytBuN2Me2S2)] (3) which is stable and can be isolated and characterized in the solid state. Complex 3 can be converted to the zinc amine function [Zn(pytBuN2H 2Me2S2)] (5) without losing the metal center using NaBH4 in methanol solution. On the other hand, complex 3 can be demetallated in an acidic medium to give the tridentate bis-benzothiazoline ligand 4. Alternatively, ligand 4 can be obtained via condensation of 3,5-di-tert-butylmercaptoaniline with 2,6-diacetylpyridine in a 2:1 molar ratio. Opening the bis-benzothiazoline ligand 4 either by reduction with NaBH 4 in methanol or by zinc acetate leads to the formation of the pentadentate dithiole-amine ligand pytBuN2H 2Me2S2-H2 (6), and the zinc imine complex 3, respectively. Ligand 6 can also be obtained via demetallation of the zinc amine complex 5 in acidic medium. All compounds have been characterized using spectroscopic methods and elemental analysis, and also by using DFT (B3LYP/6-31G) calculations in combination with experimental NMR data. © 2010 Verlag der Zeitschrift für Naturforschung, Tübingen.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Amine sulfur ligands; Dft calculations; NMR; Steric hindrance; Template synthesis; Zinc complexes